2000
DOI: 10.1080/10715760000301151
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of (-)-epicatechin upon intake of chocolate and cocoa in human volunteers

Abstract: We evaluated the levels of (-)-epicatechin (EC) and its metabolites in plasma and urine after intake of chocolate or cocoa by male volunteers. EC metabolites were analyzed by HPLC and LC/MS after glucuronidase and/or sulfatase treatment. The maximum levels of total EC metabolites in plasma were reached 2 hours after either chocolate or cocoa intake. Sulfate, glucuronide, and sulfoglucuronide (mixture of sulfate and glucuronide) conjugates of nonmethylated EC were the main metabolites present in plasma rather t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
141
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 218 publications
(161 citation statements)
references
References 14 publications
16
141
3
Order By: Relevance
“…A bioavailability study however refutes this, showing that there was no difference in the acute increases in plasma or urinary concentrations of flavanols after consumption of chocolate or dry cocoa containing the same quantities of flavanols (Baba et al, 2000). Nevertheless, when our analyses were restricted to those studies that strictly utilized dark chocolate in the active arm rather than cocoa beverages (Engler et al, 2004;Grassi et al, 2005a;Grassi et al, 2005b;Balzer et al, 2008;Almoosawi et al, 2010), we observed a stronger reduction in serum LDL concentration (À11.31 mg/dl; 95% CI was À20.79 to À1.83 mg/dl).…”
Section: Discussionmentioning
confidence: 91%
“…A bioavailability study however refutes this, showing that there was no difference in the acute increases in plasma or urinary concentrations of flavanols after consumption of chocolate or dry cocoa containing the same quantities of flavanols (Baba et al, 2000). Nevertheless, when our analyses were restricted to those studies that strictly utilized dark chocolate in the active arm rather than cocoa beverages (Engler et al, 2004;Grassi et al, 2005a;Grassi et al, 2005b;Balzer et al, 2008;Almoosawi et al, 2010), we observed a stronger reduction in serum LDL concentration (À11.31 mg/dl; 95% CI was À20.79 to À1.83 mg/dl).…”
Section: Discussionmentioning
confidence: 91%
“…Catechin was recently reported to be absorbed efficiently through the digestive tract compared to other flavonoids (22). In healthy volunteers, the intake of cocoa drinks or chocolates led epicatechin and its metabolite to reach their peak in plasma at 1 or 2 hours later (23,24). Baba et al reported the correlation of antioxidative effect and plasma epicatechin concentration in rats treated with cocoa powder (20).…”
Section: Discussionmentioning
confidence: 99%
“…For an oral administration of cocoa, approximately 25-30% of (-)-epicatechin recovered in urine was as its metabolites. 24) In addition, the maximum level in blood of (-)-epicatechin and its metabolites reached 4.77 ± 0.94 µmol/l at 2 hr after 36 g cocoa intake. (-)-Epicatechin showed antioxidative activity on LDL oxidation more than 0.5 µmol/l.…”
Section: Discussionmentioning
confidence: 99%